(3TQM fXe Cgd HOQs - (3eMeO GdeGejs ((3ehQjJGfjG s)
(3ChdgG (B:s
(3jHOC HJQLeI CHh HcQ GdUOjb Hbhdg hGPcQ CHG HcQ Hf YKeGf GdCZQ SjO Jje Jca ef cd VQQ CHhHcQ GdUOjb UGMHg GdQajb hhRjQg GdUOjb ESeg YHO Gddg Hf CHj bMGaI s
(3BNQgG (B:s
(3jfJgi HJQLeI cYH Hf YeQh GdYbHi Hbhdg GHh GdjSQ cYH Hf YeQh Hf YHGO Hf YeQhHf ZRjI ef ShGO Hf cYH Hf SdeI GdCfUGQi GdSdei s
(3HgG fXGe GdJYbjHIs
(3MhGagG ebUaI GdChGQbs
(3fSNI ecJhHI heYfhfI HGdNW GdCShO hGdNW GdCMeQ s
(3hgj YHGQI Yf fXe TYQi ai GdJGQjN s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
Keywords: (3GdJGQjNs